Let $k \in \mathbb N \setminus \{ 0 \}$. Find the limit $$\lim \bigg ( \frac 1 {n^k} \sum_{j = 1}^n j^k - \frac n {k+1} \bigg )$$

  • 2
    $\begingroup$ If it helps: this looks like integration numerics to me: if $f(x)=x^k$, your term is equal to $$n\left[\frac{1}{n}\sum_{j=1}^n f(\frac{j}{n})-\int_0^1f(t)dt\right].$$ In other words, you are looking for an equivalent of the error in the method of rectangles. $\endgroup$ – John Steinbeck Jan 23 '16 at 18:47
  • $\begingroup$ What is $\mathbb{N}^*$? $\endgroup$ – Eric Auld Jan 23 '16 at 18:57

Ok, using my comment:

$$n\left[\frac{1}{n}\sum_{j=1}^nf(\frac{j}{n})-\int_0^1f(t)dt\right]=-n\sum_j\int_{\frac{j-1}{n}}^{\frac{j}{n}}(f(t)-f(\frac{j}{n}))dt$$ $$=-n\sum_j\int_{\frac{j-1}{n}}^{\frac{j}{n}}\left(f'\left(\frac{j}{n}\right)\left(t-\frac{j}{n}\right)+f''(c_j)\left(t-\frac{j}{n}\right)^2\right)dt$$ The term $$-n\sum_j\int_{\frac{j-1}{n}}^{\frac{j}{n}}f''(c_j)\left(t-\frac{j}{n}\right)^2dt$$ clearly goes to 0 as $n$ goes to $\infty$ (using for example that $f''$ is bounded). Therefore you only focus on $$-n\sum_j\int_{\frac{j-1}{n}}^{\frac{j}{n}}f'\left(\frac{j}{n}\right)\left(t-\frac{j}{n}\right)dt=n\sum_jf'\left(\frac{j}{n}\right)\frac{1}{2n^2}$$ whose limit is $$\frac{1}{2}\int_0^1f'(t)dt$$ which is, in your case, $$\frac{1}{2}\int_0^1kt^{k-1}dt=\frac{1}{2}$$

Hoping there is no mistake, though a good point is that for $k=1$, you easily check that your sequence is constant equal to $1/2$.


Using Bernoulli's formula

$$\sum \limits _{j=1} ^n j^k = \frac 1 {k+1}\sum \limits _ {j=0} ^k {k+1\choose j} B_j (n+1)^{k+1-j}$$

and writing $\sum \limits _{j=0} ^k$ as the sum of the term with $j=0$, the term with $j=1$ and the rest of them, it is easy to note that your limit is

$$\lim \left( \frac 1 {k+1} B_0 \frac {(n+1)^{k+1}} {n^k} - \frac n {k+1} \right) + \lim B_1 \frac {(n+1)^k} {n^k} + \lim \frac 1 {n^k} \left( \frac 1 {k+1} \sum \limits _{j=2} ^k \binom {k+1} j B_j (n+1)^{k+1-j} \right) .$$

Since $B_0 = 1$, the first term is

$$\frac 1 {k+1} \lim \frac {(n+1)^{k+1} - n^{k+1}} {n^k} = \\ \frac 1 {k+1} \lim \frac {n ^{k+1} +(k+1) n^k + (\text{a finite sum of terms of smaller degree in } n) - n^{k+1}} {n^k} = 1 .$$

The second term is $B_1 = - \frac 1 2$ (look into the link given at the beginning of my answer to see the recurrence formula for Bernouli's numbers).

The third term is $0$, because the parantheses contain a finite sum of powers of $n$ smaller than the $k$-th power, so when you divide this by $n^k$ and take the limit the result is $0$.

Therefore, the result is $1 - \frac 1 2 + 0 = \color{blue} {\frac 1 2}$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.